(untitled) (UNWE Yearbook, 2020)
This study is an attempt to delineate the symbolic economy of politics as transitions – translations – transfers of economic categories into the political field. The specific transformations (inversions) that take place in the modern capitalism in the way of functioning of economic structures, leading to the spreading of capital and market motivations and phenomena as those of commodity fetishism into all social fields, and more specifically into the political field as phenomena of political fetishism. The autonomizations and heteronomizations of social fields under the pressure of capital and market forces and motivations. The mutual mediation of the economic, juridical, and political structure by the development of hybrid structures of formal equality and market freedom, of anonymous publicness of modern market and democracy. Approaches to the study of these changes are found in Pierre Bourdieu’s conceptions on the ‘symbolic economy of social practices’ and on delegation and political fetishism, as well as in Michel Foucault’s idea of ‘the market as a place of truth’ (veridiction and falsification) of the practices of governing, as formulated in his course of lectures in the Collège de France entitled ‘The Birth of Biopolitics’.